2022
DOI: 10.3390/en16010060
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Numerical Method for Calculating a Gas Supply System during a Period of Change in Thermal Loads

Abstract: Nowadays, modern gas supply systems are complex. They consist of gas distribution stations; high-, medium-, and low-pressure gas networks; gas installations; and control points. These systems are designed to provide natural gas to the population, including domestic, industrial, and agricultural consumers. This study is aimed at developing methods for improving the calculation of gas distribution networks. The gas supply system should ensure an uninterrupted and safe gas supply to consumers that is easy to oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It is conspicuous that the deformation values of the specimens are practically equal for different times of saturation with hydrogen, and there is a significant variation in the established deformation values (0.46, 0.88, and 1.2 × 10 −3 m); also conspicuous are the amounts of hydrogen released during annealing (41,117, and 137 × 10 −5 m 3 /kg) of three identical specimens (no. 1, no.…”
Section: Deformation 10 −3 M Aftermentioning
confidence: 93%
See 1 more Smart Citation
“…It is conspicuous that the deformation values of the specimens are practically equal for different times of saturation with hydrogen, and there is a significant variation in the established deformation values (0.46, 0.88, and 1.2 × 10 −3 m); also conspicuous are the amounts of hydrogen released during annealing (41,117, and 137 × 10 −5 m 3 /kg) of three identical specimens (no. 1, no.…”
Section: Deformation 10 −3 M Aftermentioning
confidence: 93%
“…The author of [39] also concludes that the lattice distortion and cold work (hardening) do increase the hydrogen absorption by steel, but reduce the diffusion of hydrogen. As a result, heat treatment used for the pipes used in underground pipelines (the removal of residual stresses/strains) [40,41] increases the diffusion of hydrogen, but reduces its absorption in the metal. (According to [39], hydrogen recombined in internal cavities can generate pressure of "several hundred atmospheres"; however, ".…”
Section: Deformation 10 −3 M Aftermentioning
confidence: 99%
“…It makes it possible to construct a temperature dependence not from one single measurement location, but from all areas of the research object. Similar works were considered in [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] but were applied to other objects. Thus, the logicality of the chosen research path was confirmed.…”
Section: The State Of Knowledge Of the Problemmentioning
confidence: 99%
“…Currently, there is a tendency to expand the scale of machine building industries (1,2). This is primarily due to the need to provide oil and gas (3)(4)(5), energy (6,7), mining (8,9) and other industries with high-performance machinery and process equipment (10,11).…”
Section: Introductionmentioning
confidence: 99%